Confidence in the future and hopelessness: Experiences in daily occupations of immigrants with late effects of polio. (January 2013) - Santos-Tavares, Iolanda; Thorén-Jönsson, Anna-Lisa
Abstract Sweden today may be described as multicultural. Those who are immigrants and have a disability are described as doubly vulnerable. Aims: To explore and describe how immigrants with late effects of polio experience their daily occupations. Method: The experiences were explored by interviews with 12 immigrants with late effects of polio, from Eastern Africa. Data analysis was carried out according to grounded theory. Results: Experiences in daily occupations affected the participants' view of the future, which in turn was influenced by the participants' conception of occupational self. This was dependent on their participation in daily occupations. Five categories influenced their experiences: rootedness in society, estimation of others, treatment by others, belonging to social networks, and the process of change in life. The social environment played an important role in determining how the participants experienced their daily occupations. Conclusions: The participants' experiences could not be seen in isolation; consequences of their disability and migration interact. The study showed that the complexity of daily life among immigrants with disability requires individual treatment and points to a need for consideration of differences in cultural background, including the therapist's own cultural lens.